2006
DOI: 10.2353/jmoldx.2006.050054
|View full text |Cite
|
Sign up to set email alerts
|

Specific Detection of Cytokeratin 20-Positive Cells in Blood of Colorectal and Breast Cancer Patients by a High Sensitivity Real-Time Reverse Transcriptase-Polymerase Chain Reaction Method

Abstract: A real-time reverse transcriptase-polymerase chain reaction (RT-PCR) method for detection of cytokeratin 20-positive cells in blood characterized by two novel features was developed and tested on 99 patients with colorectal cancer, 110 with breast cancer, and 150 healthy subjects. To optimize the specificity and sensitivity of the method, two novel features were used. First, a primer overlapping two adjacent exons was generated to inhibit nonspecific amplification both in healthy donors and cancer patients; se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 37 publications
(33 reference statements)
0
22
0
1
Order By: Relevance
“…Although the clinical significance of CTCs from patients with tumors is still debatable (12,13), the technology platform has improved rapidly. Over the last few years, CTC detection has become more standardized and reliable (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…Although the clinical significance of CTCs from patients with tumors is still debatable (12,13), the technology platform has improved rapidly. Over the last few years, CTC detection has become more standardized and reliable (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the molecular factors involved in prognosis and response to therapy in CRC is poorly understood Detection of disseminated tumour cells in peripheral blood of colorectal cancer patients has been achieved primarily using immunocytological or flow cytometry based techniques [432,433]. The clinical usefulness and high sensitivity of PCR in detecting cancer markers in circulating tumour cells was confirmed before [434,435]. In colorectal cancer, RQ-PCR was used to determine the expression levels of CEA, CK20 and CK19 mRNA in peripheral blood and indicated a valuable tool for cancer staging and disease monitoring [387,436,437].…”
Section: Discussionmentioning
confidence: 99%
“…In 11 studies, venous blood samples were used to quantify CTCs. A single [32] 2002 No 99 CR Colon: n ϭ 43; rectum: n ϭ 56 TNM stage I-III Miura et al [37] 2003 No 36 CR Dukes A-D Schuster et al [29] 2004 No 129 CR Colon: n ϭ 69; rectum: n ϭ 60 TNM stage I-IV Chen et al [34] 2004 No 42 CR Colon: n ϭ 16; rectum: n ϭ 26 TNM stage I-IV Guo et al [40] 2005 No 40 CR Dukes A-D Dandachi et al [38] 2005 No 82 CR Colon: n ϭ 42; rectum: n ϭ 40 TNM stage I-IV Giribaldi et al [41] 2006 No 99 CR TNM stage I-IV Xu et al [42] 2006 No 168 CR Dukes A-D Iinuma et al [35] 2006 Yes 167 CR Dukes A-D Friederichs et al [39] 2007 NR ϭ not reported; CK ϭ cytokeratin; CEA ϭ carcinoembryonic antigen; ProtM ϭ protease M; GCC ϭ guanylyl cyclase C; GAPDH ϭ glyceraldehyde 3-phosphate dehydrogenase; PBDG ϭ porphobilinogen deaminase; ␤-2-M ϭ ␤-2-microglobulin; RCL ϭ red cell lysis; DC ϭ density centrifugation; Pre ϭ Preoperative blood; I ϭ intraoperative blood; Po ϭ postoperative blood; Fu ϭ at follow-up; NBC ϭ nucleated blood cells; PVB ϭ peripheral venous blood; MVB ϭ mesenteric venous blood. study used blood from the radial artery [32].…”
Section: Timing and Origin Of Blood Samplementioning
confidence: 99%
“…Four different control genes were used for normalization: glyceraldehyde 3-phosphate dehydrogenase [32][33][34][35], ␤-actin [36,37], porphobilinogen deaminase [29,38,39], and ␤2-microglobulin [40]. In two studies, normalization procedure and control genes were not reported [41,42]. When identical marker and control genes were chosen for amplification, primers and probe sequence combinations differed between studies.…”
Section: Marker Genesmentioning
confidence: 99%
See 1 more Smart Citation